Solve for the variable in the following equations.
3(x^1/3)=5+2(x^1/3)
Hopefully if I've written it out right, the equation should be three times the cubed root of X equals five plus two times the cubed root of X.
What I did was subtract 2 times the cubes root of X from both sides so it looks like:
x^1/3 = 5
after that I cubed both sides and got
x=125
HOWEVER, the answer key says that the correct answer is
x= 125/4
Can anyone tell me where I keep going wrong?
3(x^1/3)=5+2(x^1/3)
Hopefully if I've written it out right, the equation should be three times the cubed root of X equals five plus two times the cubed root of X.
What I did was subtract 2 times the cubes root of X from both sides so it looks like:
x^1/3 = 5
after that I cubed both sides and got
x=125
HOWEVER, the answer key says that the correct answer is
x= 125/4
Can anyone tell me where I keep going wrong?